As relações amorosas pelos "chats" da internet: a solidão na contemporaneidade - Deziderio, Herika Regiane (2007)
The search for love relationships through chat rooms and it s feasible association to loneliness it s the purpose of this paper. The modern city life predicts by the means of concentrating people in huge buildings or by the ever-growing communication system, like the internet, a constant nearness between humans. However, despite the urban mass and the technical resources that allow greater people-to-people interactions, a forceful loss of relationship intimacy and affective and body isolation are present. This way, questions about the chat rooms and it s image of free friendship, love partnership and loneliness ending philosophy arouse. The fast typing words, the pattern of messages and the amount above the quality of the contacts are some of the free will restraining aspects to chat rooms haunters, giving them a fake feeling of freedom. Among the thousands of World Wide Web based love relations, one rarely overcomes the virtual ambience to be an actual encounter, leading us to discern a restrictive chat logic: the substitution of the pleasure by the pre-pleasure . Focused in obtain data about this study subject, two scales were built as a research instrument one for verify the search for love relationships through chat rooms and another to evaluate the chat room members loneliness those scales formed a questionnaire witch was presented to 60 persons in 20-30 years age ruled chat rooms. The results confirmed the association between loneliness and love relationship search in chat rooms. To support the analysis, we used some concepts of the critical theory of society, mainly the culture industry one, developed by Horkheimer and Adorno. The principles of shock , and the two types of Experience (Erlebnis the shallow experience and Erfahrung the profound experience) postulated by Benjamin and the freudian psychoanalysis were also used, the later in our debate about love. We concluded that the fugacity of the chat room based love relationships and the loneliness as observed on many users are also linked to objective aspects and not to a pure subjective condition